2015
DOI: 10.1103/physrevb.91.165124
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of the bulk photovoltaic effect inKNbO3and (K,Ba)(Ni,Nb)O3δ

Abstract: The connection between noncentrosymmetric materials' structure, electronic structure, and bulk photovoltaic performance remains not well understood. In particular, it is still unclear which photovoltaic (PV) mechanisms are relevant for the recently demonstrated visible-light ferroelectric photovoltaic (K,Ba)(Ni,Nb)O 3−δ . In this paper, we study the bulk photovoltaic effect (BPVE) of (K,Ba)(Ni,Nb)O 3−δ and KNbO 3 by calculating the shift current from first principles. The effects of structural phase, lattice d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…The plot for bandgap determination has two slopes, where at low photon energy the slope leads to finding the low gap of 1.85 eV, whereas at higher photon energy there is another slope that gives a gap 2.51 eV. We can speculate the reason for this phenomenon based on many previous studies [9,[16][17][18] and the schematic diagram of the intraband transition were shown in Fig. 4(b).…”
Section: Resultsmentioning
confidence: 90%
“…The plot for bandgap determination has two slopes, where at low photon energy the slope leads to finding the low gap of 1.85 eV, whereas at higher photon energy there is another slope that gives a gap 2.51 eV. We can speculate the reason for this phenomenon based on many previous studies [9,[16][17][18] and the schematic diagram of the intraband transition were shown in Fig. 4(b).…”
Section: Resultsmentioning
confidence: 90%
“…The ab initio calculation of the shift current and subsequent analysis yielded several chemical and structural criteria for optimizing the response. These criteria have been used previously to modify or identify existing materials with enhanced response [14,[32][33][34]. In this work, we use these insights to propose several candidate bulk photovoltaics with calculated response as much as an order of magnitude higher than well-known ferroelectrics, while having band gaps in or slightly below the visible spectrum.…”
mentioning
confidence: 99%
“…The shift vector R can be understood as a generalized gauge invariant k-space derivative of the p operator [32,33], and it is odd under the interchange of c and v bands. We apply this formalism to perform first-principles DFT calculations [34][35][36][37] of the shift current BPVE of the polar layered material BiTeI. This material is a normal insulator under ambient pressure, and DFT predicts that it becomes a topological insulator at pressures higher than 1.7 GPa [38].…”
mentioning
confidence: 99%
“…As such, a material with a small band gap can still have carriers emerge with more than the band gap worth of energy, as they do not thermalize before leaving the photovoltaic material. Recent works [37,[48][49][50] have studied how to achieve a large shift current magnitude in real materials, by considering structural modifications such as domain walls and chemical alloying. Our result suggests a new way to design shift current materials based on their electronic topology: to look for materials close to a band inversion transition.…”
mentioning
confidence: 99%